Telegram - Eden, Anthony, Earl of Avon, 1897-1977
010-0080-001 FZ POST OFFICE OVERSEAS TELEGRAM No. 0492 LEICESTER SQ 1 OCT 36 4237 GENEVE SDN 41001 17 1 2150 = MIDDLETON TRANSPORT HOUSE LONDRES = YOUR TELEGRAM RECEIVED REPLY WILL BE SENT AS SOON AS POSSIBLE = ANTHONY EDEN + For text of this see enclosure to letter to S. Baldwin dated 30. 9. 36. 292/946/10/86